Implementing Team-Based Post-Stroke Telerehabilitation: A Case Example - Melissa Anderson; Brad Dexter; Ana Hancock; Nealey Hoffman; Steve Kerschke; Karen Hux; Dipika Aggarwal (International Journal of Telerehabilitation)
Access to extensive, interdisciplinary rehabilitation following stroke is necessary to optimize recovery. Telerehabilitation is an appropriate model for delivering these services. However, given its relatively recent increase in popularity as a service delivery model, researchers have yet to explore the feasibility of interprofessional coordination and collaboration as a guiding framework for telerehabilitation and the effects of team-based remote service delivery on recovery of body functions and activities. This case example reports the development, implementation, and progression of a post-acute treatment program delivered via telerehabilitation to a woman with left hemorrhagic stroke. As is typical, therapy time alone afforded insufficient practice to exploit neuroplasticity and ensure maintenance and generalization of improved functioning; hence, the team worked collaboratively to encourage interdisciplinary activities outside scheduled treatment sessions. Standardized and informal assessments administered at the start and conclusion of treatment confirmed improved functioning as did the client’s progress toward independent living and return to work. Implications for telerehabilitation practices are discussed.